Pemeliharaan Cacing Sutra (Tubifex sp) dengan Dosis Pakan Organik yang Berbeda Menggunakan Sistem Resirkulasi - Bana, Adolfina Maria; Dahoklory, Nicodemus; Tobuku, Ridwan (Jurnal Aquatik, 2024)
This research lasted for 21 days and took place at the Lewa Fish Seed Center (BBI), Lewa District, Lewa Paku Village, East Sumba Regency, East Nusa Tenggara Province. This research used a Completely Randomized Design (CRD) with 5 treatments and 3 replications consisting of treatment A as control, treatment B with organic feed dose = 5 g/container, treatment C with organic feed dose = 10 g/container, treatment D with feed dose organic = 15g/container and treat E organic feed dose = 20 g/container). The parameters observed in this study were absolute weight, absolute length and water quality. Data from the Anova test results on this parameter shows that the calculated F value (0.000) < F Table 5% (54.506) so it can be concluded that the treatment was given with different doses of organic feed, namely doses of 0 g/container, 5 g/container, 10 g/ container, 15 g/container and 0 g/container have a significant effect on absolute weight. The absolute growth parameters have a real influence so it can be concluded that the provision of organic feed has a real influence on producing weight and length growth of silk worms. Keywords: Silk worms, organic feed, length, absolute growth